2023
DOI: 10.1021/acsnano.3c02290
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy Na-Deficient Layered Oxides for Sodium-Ion Batteries

Abstract: Sodium layered oxides always suffer from sluggish kinetics and deleterious phase transformations at deep-desodiation state (i.e., >4.0 V) in O3 structure, incurring inferior rate capability and grievous capacity degradation. To tackle these handicaps, here, a configurational entropy tuning protocol through manipulating the stoichiometric ratios of inactive cations is proposed to elaborately design Na-deficient, O3-type Na x TmO2 cathodes. It is found that the electrons surrounding the oxygen of the TmO6 octahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…The results showed that the Li element was successfully doped into the host phase. In addition, compared to the expected stoichiometry, the content of Na and Li is relatively low, while the proportion of other elements is close, which is attributed to the volatilization of Na and Li caused by high temperature …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The results showed that the Li element was successfully doped into the host phase. In addition, compared to the expected stoichiometry, the content of Na and Li is relatively low, while the proportion of other elements is close, which is attributed to the volatilization of Na and Li caused by high temperature …”
Section: Resultsmentioning
confidence: 84%
“…In addition, compared to the expected stoichiometry, the content of Na and Li is relatively low, while the proportion of other elements is close, which is attributed to the volatilization of Na and Li caused by high temperature. 29 Usually, microstresses within the lattice can lead to structural instability, which is detrimental to long-term cyclic stability. 30,31 The (002) peak is taken as the research object for calculating the microstress of the material based on eq 1.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution Fe 2p spectra of NFM can be divided to four peaks located at 710.4, 715.8, 723.3 and 730.7eV, which are attributed to the state of Fe 2+ and Fe 3+ [43]. The high-resolution Ti 2p spectra consists of Ti 2p3/2 peak at 457.9 eV and Ti 2p1/2 peak at 463.4 eV as well as the Na auger peak at 453.7eV, which are characteristic of Ti 4+ [44]. The Co 2p3/2, 2p1/2 peaks located at 780.3 and 795.4eV manifest that the oxidation state of Co is +3 in NFMTC [15].…”
Section: Resultsmentioning
confidence: 99%
“…The anode is pre-cycled three times before assembling the full cell due to the low coulombic efficiency of hard carbon (HC) in the first cycle. [22] Figures S17 and S18 (Supporting Information) show the rate performance and GCDs profiles of the HC anode, respectively. NaK 0.01 NMTi 0.1 O delivers a high reversible capacity of 95.5 mAh g −1 and a high average working voltage of ≈3.24 V, and can successfully illuminate commercial light-emitting diodes (Figure 2f).…”
Section: Electrochemical Performancesmentioning
confidence: 99%